The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1029/2018jg004803
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Cycle Patterns During Forest Regrowth in an African Miombo woodland Landscape

Abstract: Tropical dry forests in eastern and southern Africa cover 2.5 × 106 km2, support wildlife habitat and livelihoods of more than 150 million people, and face threats from land use and climate change. To inform conservation, we need better understanding of ecosystem processes like nutrient cycling that regulate forest productivity and biomass accumulation. Here we report on patterns in nitrogen (N) cycling across a 100‐year forest regrowth chronosequence in the Tanzanian Miombo woodlands. Soil and vegetation indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…The δ 15 N reported here for the Miombo woodland (2.68 ‰-4.32 ‰ between 0-20 cm, Fig. 2) falls within the same range as values reported by Wang et al (2013) from a moist woodland savanna in Zambia (2.6 ‰-4.8 ‰) and a mature Miombo woodland in Tanzania (3.5 ‰-3.8 ‰, Mayes et al, 2019), but they are lower compared to values reported from a dry forest in the Cerrado Savanna of Brazil (6.3 ‰-10.8 ‰, Bustamante et al, 2004).…”
Section: Using Soil δ 15 N To Assess Differences In Ecosystem N Turnoversupporting
confidence: 85%
See 1 more Smart Citation
“…The δ 15 N reported here for the Miombo woodland (2.68 ‰-4.32 ‰ between 0-20 cm, Fig. 2) falls within the same range as values reported by Wang et al (2013) from a moist woodland savanna in Zambia (2.6 ‰-4.8 ‰) and a mature Miombo woodland in Tanzania (3.5 ‰-3.8 ‰, Mayes et al, 2019), but they are lower compared to values reported from a dry forest in the Cerrado Savanna of Brazil (6.3 ‰-10.8 ‰, Bustamante et al, 2004).…”
Section: Using Soil δ 15 N To Assess Differences In Ecosystem N Turnoversupporting
confidence: 85%
“…On the other hand, fractionation during denitrification is variable with fractionation factors reported ranging from 0 ‰ to 33 ‰ (Högberg 1997). Nitrification and denitrification result in a gradual enrichment of soil δ 15 N. The process of N mineralization is believed to fractionate only marginally; however, in a system with high N mineralization rates, isotopic fractionation due to mineralization can be important (Nadelhoffer and Fry 1994). N 2 fixation depletes soil δ 15 N values, as it imports atmospheric N that has an isotopic value of 0 ‰ by default (Högberg, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The above study utilized Andosol substrates and the same experimental approach as the one presented here (nutrient deprivation). Despite the low concentration of N in the substrate used here, and taking into account that in volcanic ash-derived soils, N is limiting for plants given its low mineralization rate (Mayes et al, 2019), the deprivation of this nutrient did not affect T. rosea as drastically as the absence of other nutrients.…”
Section: Discussionmentioning
confidence: 73%